Spin slush in an extended spin ice model - Jeffrey G. Rau (Nature Portfolio, 2016)
The ultimate understanding of glassy phenomena will impact fields ranging from materials science to biophysics. Here, the authors report a heterogeneous mixture of slow relaxing spins and fast fluctuating spins, in analogy to slush as a mixture of ice and liquid water.